2016
DOI: 10.1016/j.ijscr.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic treatment of vaginal cuff dehiscence: A case report and systematic literature review

Abstract: HighlightsMinimal invasive approaches to hysterectomy, such as total laparoscopic or robotic, can lead to higher incidence of vaginal cuff dehiscence.Vaginal evisceration is a rare but life-threatening complication if it is misdiagnosed.Even if several approaches for the management of the vaginal herniation have been describe in the literature, the entirely laparoscopic treatment seems to be safe and effective, demanding nevertheless a high surgical experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…The use of laparoscopy for VCD has also been reported in the case of VCD during chemoradiation in a patient with endometrial cancer who had laparoscopic staging [10]. A case report that included a systematic review of VCD found only 3 cases (2.6%) using laparoscopy out of 116 cases reported [11]. One limitation to the use of this approach may be the need for notable technical expertise by an experienced surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The use of laparoscopy for VCD has also been reported in the case of VCD during chemoradiation in a patient with endometrial cancer who had laparoscopic staging [10]. A case report that included a systematic review of VCD found only 3 cases (2.6%) using laparoscopy out of 116 cases reported [11]. One limitation to the use of this approach may be the need for notable technical expertise by an experienced surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on VCD repair by the total laparoscopic approach describing its safety and efficacy. This is the first and second case in which total laparoscopic repair for VCD after TLmRH was performed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Among reported cases, cases of complete VCD with bowel evisceration are rare. Although there are few reports of total laparoscopic repair for VCD, 4,5 we performed this procedure in two cases. We reported two cases of complete VCD complicated by bowel evisceration after total laparoscopic modified radical hysterectomy (TLmRH), which was triggered by the first sexual intercourse after primary surgery.…”
Section: Introductionmentioning
confidence: 99%
“…La evisceración vaginal (EV) es una complicación grave posquirúrgica extremadamente rara que procede de la DCV en un 70% de los casos, representando morbilidad y mortalidad elevadas si no se diagnostica y trata a tiempo. El íleon terminal es el órgano más común de evisceración por vagina (3,4) .…”
Section: Introductionunclassified